Improving MyGRAPARI Lite ATM Services to Meet the Evolving User Needs with Increasingly Advanced Technology (Universitas Brawijaya, 2025)
This study focuses on analyzing the acceptance of MyGRAPARI Lite ATM technology at GRAPARI Telkomsel Jam Gadang Bukittinggi using the Technology Acceptance Model (TAM) which affects the level of acceptance of the technology by users. The purpose of this study is to determine the level of acceptance of MyGRAPARI Lite ATM services in the Jam Gadang Bukittinggi area in increasing the level of acceptance of the technology. This research is important because it can help Telkomsel companies improve MyGRAPARI Lite ATM services and meet the needs of users who are growing with increasingly advanced technology. The analysis method uses Partial Least Square (PLS). The selected respondents were 100 people. The data analysis used includes data quality tests, analysis of the Outer and Inner Model Structural Equation Model (SEM) and the determination of alternative hypotheses. The importance of building a positive attitude and customer satisfaction towards using MyGRAPARI system. Perceived Usefulness has a significant effect on Behavioral Intention to Use, which in turn has a significant effect on the use of the MyGRAPARI system. MyGRAPARI needs to improve services and products to meet customer needs and expectations to obtain satisfaction and improve the use of the system.